KEMAMPUAN MEMBACA PUISI SISWA KELAS VII SMP NEGERI 2 LEMBAH GUMANTI KABUPATEN SOLOK - Susanti, Welta Hadia; Eska, Wirnita; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
The background of this research there are three things: First, lack of interest and attention of students to read poetry with attention to elements of poetry readings. Second, students understand and appreciate the difficulty of reading poetry. Third, no teachers using media, such as videos of poetry readings. This study aims to describe the ability to read poetry class VII student of Junior High School Negeri 2 Lembah Gumanti Kabupaten Solok.This research is quantitative and qualitative descriptive method. The study population was all students in class VII Junior High School Negeri 2 Lembah Gumanti Kabupaten Solok., totaling 185 students. The sample was numbered VII B class (30 students). Sampling technique, which aims sample (purposive sample). This research instrument is the use of performance tests conducted by a choice of three poetry titles that have been previously determined .Based on the analysis of data, it can be seen that a qualifying acquisition of the average value of the ability to read poetry class VII B Junior High School Negeri 2 Lembah Gumanti Kabupaten Solok, viewed from the aspect of rhythm is more than enough qualifications to the acquisition value of the average 72 %, judging from aspect of the volume is in good qualification with an average acquisition value of 87 %. Aspect of this volume include the category obtained the highest level of mastery students. An examination of the expression is the value of qualified enough to gain an average of 57 % and kinesik seen from the aspect of the content of the poem is in accordance with the qualifying acquisition is less with an average value of 43 %. Generally located on more than enough qualifications to the acquisition of the average value of 2.075/30 = 69 % with a range ( 66-75 %).Therefore, it is expected to Indonesian language and literature teachers to improve their learning and reading poetry teacher should use instructional media when reading poetry, such as video displays poetry readings , in order to motivate students to read. Students are also expected to continue to practice reading poetry, so the ability to read a poem using rhythm, volume, expression, and kinesik is in perfect qualifications.